FORMULASI MINYAK-MINYAK MENGUAP MENJADI SEDIAAN BALSEM COUNTERIRRITANT - Zulkarnain, Iskandar; Aminullah, Aminullah (Fakultas Farmasi UMI, 2012)
Volatile oils have efficacy as a counterirritant. Formulation of valitel oils into counterirritant ointment preparations. The research objective of volatile oils formulations into stable dosage balm. The study conducted with qualitative examination of all the materials used. Test parameters measured are fatty oils, solubility in alcohol, the determination of optical rotation, refractive index and specific gravity. Formulation and manufacture of balm performed using the hydrocarbon base cera alba and Vaseline alba. Balm that has to be evaluated by storing at extreme temperature cycles. Parameters measured werw organoleptis examination, measurementof viscosity and yieldvalue determination, as well as examinationof heavy metal and microbial contamination. The result obtained throughout the testing on a qualitative examination of the raw material requirement. The test result organoleptic is white, odoless typical, with a appropriate consistency. Viscosity of preparation did notchange significantly. Preparation do not contain heavy metal and harmful microbes. Key Word : volatile oils, balm, stability